A theorem on diophantine approximations - Stakėnas, Vilius (Lietuvos matematikos rinkinys, 1998)
A result is proved on approximation of irrational numbers by rational ones, satisfying some requirements on their multiplicative structure. The statement is comparable with that one on diophantine approximations with square-free integers.